Genetic diversity of rice false smut fungus, Ustilaginoidea virens and its pronounced differentiation of populations in North China - Zhou, Y.-L.; Pan, Y.-J.; Xie, X.-W.; Zhu, L.H.; Xu, J.L.; Wang, S.; Li, Z.K. (Wiley, 2008)
Rice false smut caused by Ustilaginoidea virens is an important constraint affecting rice yield and quality in Asia. In China, rice false smut is especially severe in the japonica rice‐growing areas in the North China. Nothing is known neither about the diversity of the pathogen in this region nor about the characteristic of its local population. In this study, 110 U. virens isolates sampled from Liaoning and Beijing of North China were analysed using amplified fragment length polymorphism (AFLP) markers to primarily understand the genetic diversity of this pathogen and its population characteristics. At the genetic distance of 0.32, all isolates were divided into two groups. Group A consists of two subgroups differentiated at the genetic distance of 0.55, subgroup 1 included all isolates from Liaoning with an average genetic similarity over 0.82 and subgroup 2 included 27 isolates from Beijing with similarity of 0.74. Group B consists of 28 isolates from Beijing having a diversity of 0.054. The isolates from the Liaoning province, where rice false smut has generated different take‐all epidemic for 20 years, showed a genetic diversity of 0.305, which was approximately equally distributed within and among populations. Whereas genetic diversity was 0.458 among isolates from Beijing, an extremely high level of genetic differentiation among 55 isolates was observed in this disease hotspot. Our results suggested that the populations among different locations where sexual stage of the pathogen was rare to be found within ecological region were similar, and the variation of this pathogen has mainly arisen via asexual mechanisms. The migration through human activities in breeding perhaps provides a means of transporting the pathogen from one region to another.